Long-term Follow-up of BioHorizons® Implants, Placed by Postgraduate Students at the University of Barcelona, Spain - Graterol-Duran, Arianna; Ayuso-Montero, Raùl; Egido-Moreno, Sonia; Blazquez-Hinarejos, Mónica; Marí-Roig, Antonio; López-López, José (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
The study aimed to evaluate the survival and failure rate, in the short- and medium-term, in addition to its relationship with risk factors, in implants placed by postgraduate students of the Master of Medicine, Surgery, and Oral Implantology course from the University of Barcelona. The success of dental implants is related to both the surgical technique and a series of factors that can contribute to their failure over the short term. Insufficient crestal bone height or width can require regenerative surgeries that sometimes occur simultaneously with implant placement, and can lead to complications, such as soft tissue dehiscence, infections, or insufficient final bone quality. The study was designed by including 192 patients with 422 implants placed between 2015 and 2018. Variables of implant failure were evaluated and related. Failure was split into early failure and late failure. Descriptive statistical parameters were used to evaluate the variables, which included standard deviation and percentage distribution. The chi-squared test was used to compare the qualitative data, with p = 0.05 considered as a significant value, expressed in frequency distribution tables. Qualitative data were compared using the chi-squared test, taking p \(\le\) 0.05 as a significant value. The comparison of quantitative variables was carried out using the Student’s t-test for independent samples. The survival rate in a period of 6 months to 3 years was 97.87%. The mean age of the patients was (54.5 ± 13), and the largest number of implants were placed in the 51–60 age range. The failure rate was 2.13% (N = 9), 6 failed early and 3 failed after definitive prosthetic loading, with a p value < 0.0001. When comparing the failures according to their location in the anterior/posterior sector of the arch, the anterior sector showed statistically significant results (p = 0.027). Evaluating this risk factor in isolation is difficult, as other factors are in play that when taken in combination, lead to a worse prognosis of success and survival for implants. These include the patient’s systemic condition and smoking habit. Failed implants had a statistically significant relationship when they were placed in the anterior sector and were performed in the early stage. The results showed that the survival and failure rates of implants placed by postgraduate students are similar to those obtained by experienced professionals, being an effective and predictable therapy for partially or edentulous patients.